Chemical composition of a mud volcano LUSI and the health risk involved based on the air quality index that occurred as a result of disastrous gas exploration drilling activities in Sidoarjo, Indonesia - Dewi Hidayati; Ismail B.S.; Shuhaimi-Othman M.; Norela Sulaiman (Penerbit Universiti Kebangsaan Malaysia, 2018)
LUSI (Lumpur“mud”-Sidoarjo) is the mud volcanic which was initiated by the failed gas drilling exploration activities carried out near an urban area. The evaluation of the LUSI mud volcanic emission and its dried mud effects on air pollution and human health was carried out from 2011 to 2012. The concentrations of particulate matter (PM2.5), hazardous gases (H2S, SO2, NO2), volatile organic compounds (VOC): Including total hydrocarbons (THC)), toluene (C6H5CH3) and benzene (C6H6) as well as heavy metals (Pb, Cr and Cd) were measured following standard methods. The results showed that the average concentration of PM2.5 ranged from 24.0-399.9 μg/m3, H2S: 1.53-2.92 ppm; SO2: 0.021-1.321 ppm and NO2: 0.007-0.076 ppm. The VOC included total hydrocarbons from 0.57-0.96 ppm, toluene 0.33-0.92 ppm and benzene 0.33-0.40 ppm. Furthermore, heavy metal concentrations were as follows: Pb 2.6-37.34 μg/m3; Cr 0.14-12.8 μg/m3 and Cd 0.78-4.16 μg/m3. LUSI contributed to increased air pollution primarily through H2S, SO2 and PM2.5. The Air Quality Index (AQI) of PM2.5 (164-217) and SO2 (235-291) showed that the air quality at the disaster area was ‘very unhealthy’. Backward trajectories indicated that the wind direction may have had an impact on the air pollution load.